2020
DOI: 10.1098/rsbl.2019.0867
|View full text |Cite
|
Sign up to set email alerts
|

The sex with the reduced sex chromosome dies earlier: a comparison across the tree of life

Abstract: Many taxa show substantial differences in lifespan between the sexes. However, these differences are not always in the same direction. In mammals, females tend to live longer than males, while in birds, males tend to live longer than females. One possible explanation for these differences in lifespan is the unguarded X hypothesis, which suggests that the reduced or absent chromosome in the heterogametic sex (e.g. the Y chromosome in mammals and the W chromosome in birds) exposes recessive deleterious mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
107
6
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 44 publications
11
107
6
3
Order By: Relevance
“…Previously, Pipoly et al [9] identified female-biased adult sex ratios in taxa with XY systems and male-biased adult sex ratios in taxa with ZW systems. Along the same line, Xirocostas et al [10] recently found that mean/maximum lifespan is shorter in the heterogametic sex across the tree of life, although the latter could be at least partly explained by the effects of phylogenetic signal and/or sexual selection. Our results build on these studies by showing that, in vertebrates, the relationship between sex differences in survival and sex determination system remains after accounting for both phylogenetic signal (which in our sample explained ∼33% of the variance in the sex gap in lifespan) and sexual size dimorphism (a proxy for sexual selection).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previously, Pipoly et al [9] identified female-biased adult sex ratios in taxa with XY systems and male-biased adult sex ratios in taxa with ZW systems. Along the same line, Xirocostas et al [10] recently found that mean/maximum lifespan is shorter in the heterogametic sex across the tree of life, although the latter could be at least partly explained by the effects of phylogenetic signal and/or sexual selection. Our results build on these studies by showing that, in vertebrates, the relationship between sex differences in survival and sex determination system remains after accounting for both phylogenetic signal (which in our sample explained ∼33% of the variance in the sex gap in lifespan) and sexual size dimorphism (a proxy for sexual selection).…”
Section: Discussionmentioning
confidence: 91%
“…The most commonly cited hypothesis to explain broad patterns of sex-specific lifespan across taxa is the UXh hypothesis put forward by Trivers [21]. Recent work reporting a link between sex determination systems and different proxies for sex-specific lifespan have been interpreted as supporting this hypothesis [9, 10]. Here, we specifically tested for the UXh by asking whether there is a correlation between the sex-gap in survival and the relative size of the sex chromosomes (X/Z relative to Y/W and autosomes; Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations